Effect of Chinese patent medicine Si-Mo-Tang oral liquid for functional dyspepsia: A systematic review and meta-analysis of randomized controlled trials. - Yunxia Hu; Yu Bai; Zhiyun Hua; Jie Yang; Huahui Yang; Wenjun Chen; Junwei Xu; Zhiqiang Zhao (PLoS ONE)
Background Si-Mo-Tang oral liquid (SMT) has been widely used to treat functional dyspepsia (FD), but the effectiveness is still controversial. A systematic review and meta-analysis of randomized controlled trials (RCTs) were performed to assess the efficacy and adverse effects of SMT for FD. Methods Investigators searched for articles with publication dates to June 21, 2016, from 9 English and Chinese electronic databases. Comparisons were SMT alone or SMT in combination with western medicine as experimental intervention, and western medicine or placebo as the control. We used the Cochrane collaboration tool for assessing risk of bias to evaluate methodologies. Data were synthesized with RevMan 5.3 software. (PROSPERO Registration #CRD42016042003). Results Twenty-seven RCTs were included in the review, involving 2,713 participants: 1,383 subjects were in the experimental group and 1,330 in the control group. SMT showed a significant improvement in clinical efficacy (RR 1.14; 95% CI 1.09, 1.20; P<0.00001), but the heterogeneity was also significant (P = 0.0002, I2 = 56%). Because of the different interventions in the 2 groups, we performed subgroup and sensitivity analyses to investigate potential sources of heterogeneity. The heterogeneity was smaller after subgroup analysis and the exclusion of a study by Zhu from 2009. The corresponding pooled RR has no obvious change (RR 1.17; 95% CI 1.13, 1.21; P<0.00001). Subgroup analysis by age and drugs administered in control interventions between SMT and western medicine also showed improvement in the efficacy rate. But a data synthesis that excluded high risk of bias in the blinding of participants and personnel showed no significant difference (RR 1.14; 95% CI 0.97, 1.35; P = 0.12). Three studies measured gastric emptying. Two of these studies reported no significant difference between the experimental and control groups, while 1 study showed that SMT reduced the time of gastric emptying. The relapse rate and adverse effects had no difference between 2 groups. Conclusions This meta-analysis suggests that SMT is an effective and safe therapy option for patients with FD. However, because of the high clinical heterogeneity, poor quality, high risk of bias and small sample size of some included studies, further standardized large-scale and strictly designed studies are needed.